ANALISIS PENGGUNAAN METODE ROOT SHELL EXPLOIT DALAM PROSES FLASHING FIRMWARE OPENWRT PADA PERANGKAT XIAOMI MI ROUTER 4A - haryanto, Edy; Jarir, Jarir (Jurnal Education and Information Technology, 2023)
This research aims to optimize the hardware performance of the Xiaomi MI Router 4A by replacing the original firmware with OpenWrt firmware. The original firmware of the router has inherent feature limitations, and the adoption of OpenWrt firmware is anticipated to enhance the router’s capabilities. However, the conventional firmware replacement process typically necessitates physical access to the ROM and direct reprogramming, which is impractical and carries the risk of hardware damage. Hence, this study employs the root shell exploit method to remotely install firmware via the network, eliminating the need for physical interaction with the ROM. This method is expected to facilitate the firmware installation process and mitigate the risk of hardware damage. The research provides insights into the utilization of the root shell exploit method for firmware replacement on the Xiaomi MI Router 4A, while also offering practical recommendations for users seeking to optimize their router’s performance through the utilization of OpenWrt firmware.